Quaternary River Diversions in the London Basin and the Eastern English Channel - Bridgland, D.; Gibbard, P. (Géographie physique et Quaternaire, 1997)
ABSTRACTThe principal river of the London basin, the Thames, has experienced a number of course changes during the Quaternary. Some, at least, of these are known to result directly from glaciation. In the early Quaternary the river flowed to the north of London across East Anglia to the north coast of Norfolk. By the early Middle Pleistocene it had changed its course to flow eastwards near the Suffolk - Essex border into the southern North Sea. The Thames valley to the north of London was blocked by ice during the Anglian/Elsterian glaciation, causing a series of glacial lakes to form. Overflow of these lakes brought the river into its modern valley through London. It is thought that this valley already existed by the Anglian in the form of a tributary of the north-flowing River Medway, which joined the old Thames valley near Clacton. Also during the Anglian/Elsterian glaciation. British and continental ice masses are thought to have joined in the northern part of the North Sea basin, causing a large lake to form between the east coast of England and the Netherlands. It is widely believed that the overflow from this lake caused the first breach in the Weald-Artois Ridge, bringing about the formation of the Strait of Dover. Prior to the glaciation the Thames, in common with rivers from the continent (including the Rhine and Meuse), flowed into the North Sea Basin. It seems that, after the lake overflow, these rivers together drained southwards into the English Channel. Whether this southern drainage route was adopted during all later periods of low sea level remains to be determined, but it seems certain that this was the case during the last glacial.